2012
DOI: 10.1002/art.34381
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgG on cell‐derived plasma microparticles in systemic lupus erythematosus is associated with autoantibodies and complement activation

Abstract: Objective. To quantify immunoglobulin and C1q on circulating cell-derived microparticles (MPs) in patients with systemic lupus erythematosus (SLE) and to determine whether immunoglobulin and C1q levels are correlated with clinical and serologic parameters.Methods. Sixty-eight clinically well-characterized SLE patients, 38 healthy controls, 6 patients with systemic sclerosis (SSc), and 6 patients with rheumatoid arthritis (RA) were included. The numbers of annexin V-binding MPs displaying IgG, IgM, or C1q were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 51 publications
9
147
1
Order By: Relevance
“…Although immunoglobulin and complement proteins have been detected on the surface of microparticles from apoptotic cells 14 and microparticles isolated from patients with inflammatory diseases, [15][16][17] these previous studies did not Microparticles from the supernatant of unmanipulated or CsA-treated cells were exposed to serum, and C3 deposition on the microparticles was assessed by Western blot analysis using a polyclonal antibody to C3 and a monoclonal antibody to C3d. The a92 band of C3 (representing the iC3b form) and C3d were readily detected on microparticles from CsA-treated cells that were exposed to serum (MP, microparticle; NMS, normal mouse serum; S, serum).…”
Section: Discussionmentioning
confidence: 91%
“…Although immunoglobulin and complement proteins have been detected on the surface of microparticles from apoptotic cells 14 and microparticles isolated from patients with inflammatory diseases, [15][16][17] these previous studies did not Microparticles from the supernatant of unmanipulated or CsA-treated cells were exposed to serum, and C3 deposition on the microparticles was assessed by Western blot analysis using a polyclonal antibody to C3 and a monoclonal antibody to C3d. The a92 band of C3 (representing the iC3b form) and C3d were readily detected on microparticles from CsA-treated cells that were exposed to serum (MP, microparticle; NMS, normal mouse serum; S, serum).…”
Section: Discussionmentioning
confidence: 91%
“…This is not the first time an autoantigen has been identified on MVs. Studies examining other autoimmune diseases including rheumatoid arthritis and systemic lupus erythematosus have found that autoantigens are expressed on MVs and that these MVs can form potent inflammatory complexes containing autoantibodies (55,56). This phenomenon may also contribute to inflammation in GPA, although more research is required to determine whether these complexes form when MVs are produced from a PR3-expressing cell.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, plasma EVs from systemic lupus erythematous (SLE) were shown to not only contain self antigens (69,70), but also to interact with IgG, IgM, and complement proteins. However, it was not clear whether these interactions represent true immune complexes (71)(72)(73). Additionally, EVs enhance autoimmune phenotypes through secretion or surface expression of proinflammatory cytokines that promote an inflammatory environment and autoreactive T cell survival (74,75).…”
Section: The Role Of Evs In Autoimmunitymentioning
confidence: 99%